Investigar la comunicación en Loja-Ecuador - Yaguache, Jenny (Chasqui. Revista Latinoamericana de Comunicación, 2015)
Autores: J.P. Suárez, X. López, L. González, M. I. Punín, A. Suing, C. Mier, J. Yaguache, K. Valarezo, C. Granda, M. Otero, D. Rivera, G. Coronel, B. García, V. González, C. Ortíz, P. Barrazueta, F. Paladines, X. Soengas, H. Yaguana. Edición: X. R. Pousa & F. Campos. Ciudad: Loja Editorial: Ediloja Año: 2009 ISBN: 978-9942-00-685-1 Páginas: 325